2010
DOI: 10.1111/j.1365-2702.2009.03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived aggression towards nurses: study in two Italian health institutions

Abstract: AIMS: The goal of the present study was to quantify the perceived aggression towards nurses working in two Italian health care institutions and to verify the hypothesis of an association between the characteristics of aggressors and the type of aggression. BACKGROUND: Violence and aggressiveness, particularly aimed at nurses, are a common, but inadequately investigated phenomenon in Italian health care institutions. DESIGN: A cross-sectional study. METHODS: The study was performed, studying a sample of 700 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
99
3
31

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(142 citation statements)
references
References 44 publications
9
99
3
31
Order By: Relevance
“…In addition to these measures, certain studies have also suggested that policy by management against violence, educating patients and their families, effective communication, security and alarm systems, restricting public access and controlling visiting times, and adequate staff numbers can also be helpful in preventing the incidents of violence. 33,37,47,[49][50][51][52][53] Since most of the respondents in the current study and other studies perceive that the incidents of violence are preventable, this also suggests that there is an unmet need for the protective systems to be in place. 33 The lack of knowledge and the skill to handle these situations has been cited as the reason for violent incidents.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to these measures, certain studies have also suggested that policy by management against violence, educating patients and their families, effective communication, security and alarm systems, restricting public access and controlling visiting times, and adequate staff numbers can also be helpful in preventing the incidents of violence. 33,37,47,[49][50][51][52][53] Since most of the respondents in the current study and other studies perceive that the incidents of violence are preventable, this also suggests that there is an unmet need for the protective systems to be in place. 33 The lack of knowledge and the skill to handle these situations has been cited as the reason for violent incidents.…”
Section: Discussionmentioning
confidence: 90%
“…The same result was evidenced in a research undertaken at the hospital emergency sector in Natal -RN (8) . This finding may be explained by the fact that these professionals are subject to greater psychological demands in the nursing team (15) , making them more tired, stressed and dissatisfied, and at greater risk of suffering violence at work by colleagues, patients and companions (14) . In function of their education, nurses may also develop a greater ability to reflect on their work process, perceive their job conditions and be sensitive to situations of violence (8) .…”
Section: Discussionmentioning
confidence: 95%
“…A hostile work environment can significantly affect workers though, making them feel annoyed offended, very sad (9) and angry (14) . Further consequences may happen, such as decreased performance and dissatisfaction at work, absenteeism, transfers, resignations, fear of patients (14) , feeling of low self-esteem, depression, anxiety, fatigue, irritability, sleep and eating disorders (4) . The exact long-term consequences for the performance and morale of nursing professionals who work in a violent environment are not known clearly yet though (9) .…”
Section: Discussionmentioning
confidence: 99%
“…10 It varied from place to place ranged from 10 to 95 percent in many countries worldwide. 3,7,[11][12][13][14][15] Thus this study aimed to assess the prevalence of workplace violence and its associated factors among nurses in Pokhara, Nepal.…”
Section: Introductionmentioning
confidence: 99%